Sarcopenia: a geriatric syndrome that impacts urology - Heppner, Hans Jürgen; Hag, H. (Urologe, 2021)
With increasing age, people lose muscle strength and muscle mass. Acute illnesses, surgical interventions or chronic illnesses can quickly lead to immobility and even more muscle loss. For the elderly, there is a risk of reduced functionality and everyday skills. This syndrome, referred to sarcopenia, is characterized by a progressive and generalized loss of muscle mass and strength with negative consequences such as functional impairment and frailty. In the case of serious illnesses or surgical interventions, this is particularly noticeable in prolonged convalescence. Sarcopenia is associated with reduced quality of life and increased mortality. It is important to diagnose sarcopenia with the help of specific anamnesis questions and clinical functional examinations and to initiate adequate interventions, if possible preoperatively, for example. In addition to treating the underlying disease, it is crucial to always pay attention to the combination of a balanced protein-rich diet and appropriate physical training. Use of only one of the components or even the drug therapy approach is not effective.
CRIS-Team WoS Importer:2021-11-19